Ahammiyyah Istikhdām al-Wasāʾil al-Taʿlīmiyyah fī Taʿlīm al-Lughah al-ʿArabiyyah li al-Nāṭiqīn bi-Ghayrihā - Umar Faruq (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2014)
Language is a fundamental means of communication through which people express their identities, interests, talents, knowledge, thoughts, and emotions. However, learning a foreign language, including Arabic, presents numerous challenges for non-native speakers. Although Arabic language instruction for non-native learners has expanded in many parts of the world, the level of success achieved has generally remained below expectations. The effectiveness of Arabic language teaching is still relatively limited due to various obstacles encountered by both teachers and learners. The use of instructional media is considered one of the most effective solutions to address these challenges. Teachers’ creativity in selecting and utilizing instructional media that is appropriate to specific language elements and language skills plays a crucial role in improving the effectiveness of Arabic language teaching and learning. Therefore, this article discusses the importance of instructional media in teaching Arabic to non-native speakers, emphasizing its ability to create a more active, innovative, engaging, and enjoyable learning environment.